Title analysis of (systematic) scoping review studies: Chaos or consistency? - Chrastina, Jan (Nursing & health sciences, 2020)
The scoping review is one of the alternatives of producing a literature review. However, this approach still lacks a clearly accepted definition, and the scoping terminology is also somewhat fuzzy. Although the methodology of scoping review processing is relatively uniform, terminological chaos appears in the titles of studies with scoping review methodology. This paper presents an analysis of selected published studies with a focus on the content of their titles. A total of 13 thematic dimensions were identified covering the content of titles that show a degree of inconsistency and frequent terminological and methodological "chaos." This study includes a broad scope of themes and areas for which scoping reviews were produced. We would like to recommend to authors (especially scoping review beginners) to - if not necessary or desirable - avoid introducing new concepts and specifications of titles of produced and published scoping review studies. In the case of literature reviews and knowledge synthesis it is necessary to search according to specific keywords and search phrases - more fragmented scoping review terminology makes literature search more difficult or even impossible.
Keywords: výzkumný projekt; Scoping Reviews As Topic; nursing research; lidé; scoping review; terminology; Humans; scoping review jako téma; Research Design; title analysis